ECOWAS Protocol on Migration, Porous Borders and Dynamics of Armed Banditry in Nigeria - Obikaeze, Chibuike Victor; Efanodor-Obeten, Omokiniovo Harriet; Inah, Emmanuel Mkpe (Journal of Contemporary International Relations and Diplomacy, 2023)
The dialectics that have led to an explosion of free movement of persons within ECOWAS borders largely constitute a new dimension of security threats in the region. The security threats emanating from incessant human migration within the region have predictably distorted the security architecture of Nigeria, thereby posing colossal pressures on the Nigerian armed forces, as well as leading to the loss of human lives, properties, and financial resources. The study investigated how ECOWAS protocol on free movement of persons and porous borders in the West African region orchestrate armed banditry in Nigeria. The work was anchored on the Qualitative-Descriptive method of analysis, and ‘inelastic political will’ was adopted as an analytical construct that explains the inability of ECOWAS member governments as well as the Nigerian government to employ sustainable strategies in tackling the ever-changing security threat dimensions within the region. It was revealed that chaotic and explosive cross-border migration of persons in West Africa has a relationship with the new dimension of armed banditry in Nigeria. The study recommended that the ECOWAS framework that promotes the free movement of people be reviewed and amended to address current security crises in the region. Also, there is a need for the Nigerian government to reinforce viable and strong diplomatic ties with the neighboring countries such as Benin, Chat, Niger, and Cameroon regarding border infrastructure development and security enhancement mechanisms to cover ungoverned spaces in the Chad Basin Region.